2018
DOI: 10.3390/molecules23092112
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from Euphorbia maculata and Their Anti-Inflammatory Effects

Abstract: Euphorbia maculata is a medicinal plant of the Euphorbiaceae family, which can produce anti-inflammatory and cancer chemopreventive agents of triterpenoids. The present study reports on the bioactive triterpenoids of this plant. Two new lanostane-type triterpenoids, named (3S,4S,7S,9R)-4-methyl-3,7-dihydroxy-7(8→9) abeo-lanost-24(28)-en-8-one (1) and 24-hydroperoxylanost-7,25-dien-3β-ol (2), together with 15 known triterpene derivatives, were isolated from Euphorbia maculata. The structures of the new compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…PRI is a natural triterpenoid compound extracted from plants of the Celastraceae and Hippocrateaceae family. PRI has attracted much attention over the years for its chemopreventive and chemotherapeutic properties, 24 anti-inflammatory, anti-oxidant, anti-arthritic, anti-malarial, anti-viral, anti-bacterial activities, 12 , 15 , 25 , 26 and anti-tumour effects against breast cancer, lung cancer, prostate cancer, cervical cancer, gliomas, leukemias, and multiple myeloma tumors. 14 , 27 , 28 Based on the results presented in this study, we now add anti-osteoclastic and anti-resorptive properties to the list of biological effects exerted by PRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRI is a natural triterpenoid compound extracted from plants of the Celastraceae and Hippocrateaceae family. PRI has attracted much attention over the years for its chemopreventive and chemotherapeutic properties, 24 anti-inflammatory, anti-oxidant, anti-arthritic, anti-malarial, anti-viral, anti-bacterial activities, 12 , 15 , 25 , 26 and anti-tumour effects against breast cancer, lung cancer, prostate cancer, cervical cancer, gliomas, leukemias, and multiple myeloma tumors. 14 , 27 , 28 Based on the results presented in this study, we now add anti-osteoclastic and anti-resorptive properties to the list of biological effects exerted by PRI.…”
Section: Discussionmentioning
confidence: 99%
“…Pristimerin (PRI) is a natural quinone-methide triterpenoid compound extracted from plants of the Celastraceae and Hippocrateaceae family and exerts multiple pharmacological activities with its anti-inflammatory 12 and anti-cancer properties 13 the most studied. It has been demonstrated that PRI induces apoptosis via the Akt/NF-κB and ROS/MAPK signal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Euphorbia is the largest genus of the Euphorbiaceae family, with species containing cytotoxic, antibacterial, antifungal, antiparasitic, antitumor, anti-inflammatory, mosquito larvicidal and anti-Alzheimer's triterpenes. [12][13][14][15][16][17][18] Derivatives from the conventional oxidation of triterpenes isolated from the latex of Euphorbia officinarum and Euphorbia resinifera have demonstrated strong postingestive toxic effects on the insect pest Spodoptera littoralis, selective cytotoxicity on insect and mammalian cells [19] and antiparasitic effects on two protozoan species, Leishmania infantum and Trypanosoma cruzi. [20] Furthermore, some of these derivatives protected tomato plants from Verticillium dahliae at low concentrations, elicited H 2 O 2 , and increased the activity of antioxidant enzymes suggesting elicitor-like effects [21,22] with similar action on Nicotiana benthamia against Pseudomonas syringae.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Terpenoids have anti-inflammatory and anti-tumor effects (8)(9)(10)(11), and PM has been reported to show anti-inflammatory and antioxidant effects (12,13). In addition, PM has been reported to have anti-tumor effects on lung cancer, breast cancer, prostate cancer, uterine cancer, gliomas, and leukemias (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%